ANALISIS PERUBAHAN GARIS PANTAI DI WILAYAH PESISIR PROVINSI RIAU MENGGUNAKAN DATA SATELIT - Rizki Ramadhan Husaini; Muhammad Yazid; Husni Mubarak; Tri Ramadani; Muhammad Hanif Ahda; Muhammad Fajar Anugrah (LPPM Universitas Abdurrab, 2023)
Riau Province has a coastline area estimated at 2,713 kilometers. Changes in the coastline in the coastal areas of Riau Province occur along the current coastline. This change has an impact on the country's border zones and reduces the quality of life of the people who live around these areas. This research aims to determine the distance and rate of change in coastlines, as well as maximum changes in abrasion and accretion. Calculation of coastline changes using satellite data processed through the Digital Shoreline Analysis System (DSAS) application with Net Shoreline Movement (NSM) and End Point Rate (EPR) statistical methods as well as discussion of aspects of land cover, wind direction, soil type and 10 year statistics going forward by taking research time in 2013, 2017 and 2021. The highest area of abrasion occurred in Rangsang District at 1760.04 ha with a rate of 25.82 m/year while the highest accretion area occurred in Sinaboi District at 2195.55 ha at a rate of 87, 24 m/year.